Transcription Factor RUNX1 Regulates Platelet PCTP (Phosphatidylcholine Transfer Protein): Implications for Cardiovascular Events: Differential Effects of RUNX1 Variants - Mao, Guangfen; Songdej, Natthapol; Voora, Deepak; Goldfinger, Lawrence E.; Del Carpio-Cano, Fabiola E.; Myers, Rachel A.; Rao, A. Koneti (Circulation (New York, N.Y.), 2017)
BACKGROUND:PCTP (phosphatidylcholine transfer protein) regulates the intermembrane transfer of phosphatidylcholine. Higher platelet PCTP expression is associated with increased platelet responses on activation of protease-activated receptor 4 thrombin receptors noted in black subjects compared with white subjects. Little is known about the regulation of platelet PCTP. Haplodeficiency of RUNX1, a major hematopoietic transcription factor, is associated with thrombocytopenia and impaired platelet responses on activation. Platelet expression profiling of a patient with a RUNX1 loss-of-function mutation revealed a 10-fold downregulation of the PCTP gene compared with healthy controls. METHODS:We pursued the hypothesis that PCTP is regulated by RUNX1 and that PCTP expression is correlated with cardiovascular events. We studied RUNX1 binding to the PCTP promoter using DNA-protein binding studies and human erythroleukemia cells and promoter activity using luciferase reporter studies. We assessed the relationship between RUNX1 and PCTP in peripheral blood RNA and PCTP and death or myocardial infarction in 2 separate patient cohorts (587 total patients) with cardiovascular disease. RESULTS:Platelet PCTP protein in the patient was reduced by ≈50%. DNA-protein binding studies showed RUNX1 binding to consensus sites in ≈1 kB of PCTP promoter. PCTP expression was increased with RUNX1 overexpression and reduced with RUNX1 knockdown in human erythroleukemia cells, indicating that PCTP is regulated by RUNX1. Studies in 2 cohorts of patients showed that RUNX1 expression in blood correlated with PCTP gene expression; PCTP expression was higher in black compared with white subjects and was associated with future death/myocardial infarction after adjustment for age, sex, and race (odds ratio, 2.05; 95% confidence interval 1.6–2.7; P<0.0001). RUNX1 expression is known to initiate at 2 alternative promoters, a distal P1 and a proximal P2 promoter. In patient cohorts, there were differential effects of RUNX1 isoforms on PCTP expression with a negative correlation in blood between RUNX1 expressed from the P1 promoter and PCTP expression. CONCLUSIONS:PCTP is a direct transcriptional target of RUNX1. PCTP expression is associated with death/myocardial infarction in patients with cardiovascular disease. RUNX1 regulation of PCTP may play a role in the pathogenesis of platelet-mediated cardiovascular events.